Improved biorefinery pathways of marine diatoms using a water miscible ionic liquid and its colloidal solution: efficient lipid extraction and in situ synthesis of fluorescent carbon dots for bio-imaging applications. Issue 35 (22nd June 2021) - Krishna, Paidi Murali; Polisetti, Veerababu; Damarla, Krishnaiah; Mandal, Subir Kumar; Kumar, Arvind
Abstract : In this study, a water-miscible ionic liquid (IL), 1-ethyl-3-methylimidazoliumacetate ([EMIM][Ac]), has been used for lipid extraction from marine diatoms Thalassiosira lundiana CSIR-CSMCRI 001 by following a non-polar solvent partition method. Abstract : In this study, a water-miscible 'classic' ionic liquid (IL), 1-ethyl-3-methylimidazoliumacetate ([EMIM][Ac]), has been used for lipid extraction from marine diatoms Thalassiosira lundiana CSIR-CSMCRI 001 by following a non-polar solvent partition method. The composition of lipid was determined using gas chromatography-mass spectrometry (GC-MS). In total, 91.4 mg g −1 (dry wt) of lipid was produced, out of which the percentage of docosahexaenoic acids (DHA), myristic acid, palmitic acid, and arachidonic acid was 19.6%, 15.1%, 11.2%, and 10.4%, respectively. The IL-inseparable residual waste solution was directly used to generate green fluorescent carbon dots (FCDs) by constructing a colloidal solution with the help of a surface-active IL, choline dioctyl sulfosuccinate ([Cho][AOT] ). The stability of colloidal FCDs was examined using FTIR, FT-NMR, and Raman spectroscopy. FCDs were extracted from the colloidal solutions via the demicellization process and characterized using HR-TEM (2 to 5 nm) and PXRD techniques. The optical properties of colloidal FCDs were measured using UV-Vis and fluorescence spectroscopy and showed a wide range of emission ( λ 460 nm to λ 590 nm ). Such FCD stabilized colloidal solutions could be effectively used in fluorescence imaging of yeast cells, thus making the biorefinery approach more sustainable.